2015
DOI: 10.3201/eid2107.141980
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Range Expansion for Rat Lungworm in North America

Abstract: Using quantitative PCR analysis and DNA sequencing, we provide evidence for the presence of rat lungworm (Angiostrongylus cantonensis) in Oklahoma, USA, and identified a potentially novel rat host (Sigmodon hispidus). Our results indicate a geographic range expansion for this medically and ecologically relevant parasite in North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…In Louisiana, two R . norvegicus were found positive and in Oklahoma, one Sigmodon hispidus was found positive (total 2.2% or 3/137 brain samples) [ 22 ]. However in this study, we observed 72.7% (396/545) of Rattus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Louisiana, two R . norvegicus were found positive and in Oklahoma, one Sigmodon hispidus was found positive (total 2.2% or 3/137 brain samples) [ 22 ]. However in this study, we observed 72.7% (396/545) of Rattus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies use PCR to document presence/absence of A . cantonensis in rats [ 15 , 1 , 22 , 9 ], but since this method reports any presence of the parasite DNA, it does not distinguish between life stages. In other words, identifying the infection levels of adult worms in rat populations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of newly invaded territories keep occurring, e.g. Canary Islands (2010), Uganda (2012) and Oklahoma, USA (2015), although the exact timing and the route of the invasions remains largely uncharacterised [2426].…”
Section: Introductionmentioning
confidence: 99%
“…1518 In the United States, angiostrongyliasis has been present in Hawaii since at least 1959. 19,20 However, recently, A. cantonensis has been found in both mollusk and rat hosts in the Gulf Coast region of the continental United States, 2123 and sporadic autochthonous cases have been identified in other areas as well. 24,25 This suggests the range of the parasite continues to expand, and cases may continue to appear in regions previously unaffected.…”
Section: Introductionmentioning
confidence: 99%